问题 解答题
(1)计算:
1
2
+(-
2
3
)+
4
7
+(-
1
2
)+(-
1
3
)

(2)计算:(-2)4÷(-2
2
3
)2+5
1
2
×(-
1
6
)-0.25

(3)先化简,再求:(2a2-5a)-2(3a+5+a2)的值,其中a=-1
(4)解方程:1-
x-1
2
=2-
x+2
3
答案

(1)

1
2
+(-
2
3
)+
4
7
+(-
1
2
)+(-
1
3
)

=(

1
2
-
1
2
)+(-
2
3
-
1
3
)+
4
7

=0-1+

4
7

=-

3
7

(2)(-2)4÷(-2

2
3
)2+5
1
2
×(-
1
6
)-0.25

=16÷

64
9
-
11
12
-
1
4

=2

1
4
-
1
4
-
11
12

=2-

11
12

=1

1
12

(3)(2a2-5a)-2(3a+5+a2

=2a2-5a-6a-10-2a2

=-11a-10

当a=-1时,原式=11-10=1;

(4)1-

x-1
2
=2-
x+2
3

6-3(x-1)=12-2(x+2),

6-3x+3=12-2x-4,

-x=-1,

x=1.

单项选择题 B1型题
单项选择题